Effects of microRNA-208a on inflammation and oxidative stress in ketamine-induced cardiotoxicity through Notch/NF-κB signal pathways by CHD9. Issue 5 (17th May 2019) - Yuan, Hongjie; Du, Shibin; Deng, Youliang; Xu, Xiaoqing; Zhang, Qian; Wang, Miao; Wang, Ping; Su, Yi; Liang, Xiao; Sun, Yanyan; An, Zhengzhuang
Abstract : Background: MicroRNA can regulate gene expression, and participate in multiple vital activities, such as inflammation, oxidative stress epigenetic modification, cell proliferation, and apoptosis. It plays an important role in the genesis and development of cardiovascular disease. Objective: To assess the role of microRNA-208a in ketamine-induced cardiotoxicity. Methods: All rats were randomly selected into two groups: sham and model groups. After fixed, all rats in the model group was intraperitoneally (IP) injected with 100 mg/kg of ketamine. Heart samples were stained with HE assay. Total RNAs from serum were used to hybridize with the SurePrint G3 Rat Whole Genome GE 8×60 K Microarray G4858A platform. Results: In the rat model with ketamine-induced cardiotoxicity, microRNA-208a expression was increased. Then, over-expression of microRNA-208a increased inflammation and oxidative stress in vitro model. However, down-regulation of microRNA-208a decreased inflammation and oxidative stress in vitro model. Over-expression of microRNA-208a suppressed CHD9 and Notch1, and induced p65 protein expression in vitro model. Overexpression of CHD9 reduced the effects of microRNA-208a on inflammation and oxidative stress in heart cell through Notch/p65 signal pathways. Notch1 activation reduced the effects of microRNA-208a on inflammation and oxidative stress in heart cell through p65 signal pathways. Conclusion: MicroRNA-208a may be a potential biomarker for ketamine-induced cardiotoxicity through inflammation and oxidative stress by Notch/NF-κB signal pathways by CHD9.